Tinker, Tailor, Tumour Suppressor: The Many Functions of PRP4K - Habib, Elias B.; Mathavarajah, Sabateeshan; Dellaire, Graham (Frontiers in Genetics, 2022)
Pre-mRNA processing factor 4 kinase (PRP4K, also known as PRPF4B) is an essential kinase first identified in the fission yeast Schizosaccharomyces pombe that is evolutionary conserved from amoebae to animals. During spliceosomal assembly, PRP4K interacts with and phosphorylates PRPF6 and PRPF31 to facilitate the formation of the spliceosome B complex. However, over the past decade additional evidence has emerged that PRP4K has many diverse cellular roles beyond splicing that contribute to tumour suppression and chemotherapeutic responses in mammals. For example, PRP4K appears to play roles in regulating transcription and the spindle assembly checkpoint (SAC), a key pathway in maintaining chromosomes stability and the response of cancer cells to taxane-based chemotherapy. In addition, PRP4K has been revealed to be a haploinsufficient tumour suppressor that promotes aggressive cancer phenotypes when partially depleted. PRP4K is regulated by both the HER2 and estrogen receptor, and its partial loss increases resistance to the taxanes in multiple malignancies including cervical, breast and ovarian cancer. Moreover, ovarian and triple negative breast cancer patients harboring tumours with low PRP4K expression exhibit worse overall survival. The depletion of PRP4K also enhances both Yap and epidermal growth factor receptor (EGFR) signaling, the latter promoting anoikis resistance in breast and ovarian cancer. Finally, PRP4K is negatively regulated during epithelial-to-mesenchymal transition (EMT), a process that promotes increased cell motility, drug resistance and cancer metastasis. Thus, as we discuss in this review, PRP4K likely plays evolutionarily conserved roles not only in splicing but in a number of cellular pathways that together contribute to tumour suppression.